Role of human resource flexibility in organisational performance: a study of Indian IT firms. (2017) - Kumar, V.V. Ajith; Rai, Snigdha
Present study examines the direct relationship between HR flexibility and organisational performance. Also this study explores the moderating role of ethical culture in the relationship of HR flexibility and organisational performance. Data was collected via a questionnaire survey of 126 employees working in 65 major IT companies of Bangalore. The results indicate that all three dimensions of HR flexibility (skill flexibility, behavioural flexibility and HR practice flexibility) were significantly positively correlated with organisational performance (HR-related performance and financial performance). Results of moderated regression analysis reveal the significant moderating role of ethical culture in HR flexibility and HR performance relationship. Limitations of the study and implications of the results are also discussed.